Implicit Contracts and the Cyclicality of the Skill-Premium - Panayiotis M. Pourpourides (Cardiff University, Cardiff Business School, 2010)
To examine the cyclical behavior of the skill-premium, this paper introduces implicit labor contracts in a DSGE model where production is characterized by capital-skill complementarity and the utilization of capital is endogenous. It is shown that this model can reproduce the observed cyclical patterns of wages and the skill-premium. The feature of capital-skill complementarity coupled with variable capital utilization rates does not come at odds with the acyclical behavior of the skill-premium. The paper argues that the skill-complementarity of capital is not a quantitatively signiÖcant factor at high frequencies. The key aspects are the contracts and the capital utilization margin.
Keywords: E13; E24; E32; 330; Implicit Contracts; Wages; Skill-Premium; Business Cycles; CapitalSkill Complementarity; Lohndifferenzierung; Qualifikation; Konjunktur; Allgemeines Gleichgewicht; Lohntheorie